Pengaruh Biaya Produksi Padi, Harga Gabah, dan Distribusi Beras Terhadap Harga Beras di Indonesia Tahun 2017-2024 - Diary Natama; Karuniana Dianta A.S; Dicky Iranto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of paddy production cost, grain price, and rice distribution on rice price in Indonesia. A quantitative approach was employed using panel data regression analysis to examine the effects of the independent variables paddy production cost, grain price, and rice distribution on the dependent variable, namely rice prices at the consumer level. Secondary data were obtained from the Central Statistics Agency (BPS) and the Agricultural Data and Information System Center of the Ministry of Agriculture, covering 32 provinces over the 2017–2024 period. The analysis was conducted using the Random Effects Model (REM) with the assistance of EViews version 12 software. The results indicate that paddy production costs and grain prices have a positive and significant effect on rice prices, suggesting that increases in these two variables tend to drive rice prices upward. In contrast, rice distribution does not exert a significant influence on rice prices, indicating that logistics and distribution factors have not yet emerged as dominant determinants in rice price formation. These findings underscore the importance of government policies aimed at controlling production costs and stabilizing grain prices to ensure the affordability of rice for consumers